Amyand’s hernia in infant: A rare entity - Upadhyaya, VD; Kumar, V; Srivastava, P; Gangopadhyaya, AN (Kathmandu University Medical Journal, 2010)
The chance of vermiform appendix lying with in a hernial sac is 1% or less and is known as Amyand's hernia and it is very rare in infant and neonate. Till date, only twenty cases had been reported in English literature. We are reporting a rare case of Amyand's hernia where appendix was present in right inguinal sac of non-obstructed inguinal hernia in a seven month old male infant during operation. The appendectomy was done along with right inguinal herniotomy. In most of the reported cases, appendix was inflamed or perforated, expect in one case where appendix was not inflamed but patient presented with inguinal hernia. This case is reported because of the rarity of Amyand's hernia in infant, the appendix was not inflamed, hernia was not obstructed, and whether in such types of cases appendix should be preserved or not. Key words: Amyand's hernia; infant; appendectomy DOI: 10.3126/kumj.v7i2.2708 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 143-144